Predictors of Organizational Citizenship Behaviors (OCB), The Moderating and Mediating Roles of Mentoring and Perceived Organizational Support in The Power Holding Company (PHCN) of Nigeria (Global Business Management Review (GBMR), 2022)
This paper presents a model for motivating employees to engage in OCB through the role of transactional leadership, organizational justice, and psychological ownership mediated by the workers’ perceived organizational support, and moderated by the mentoring function. Organizational citizenship behaviors (OCB) which is discretionary, and not part of an employee’s formal job requirement promotes the effective functioning of organizations. Theoretically, this study aims to elaborately contribute to organizational behavior literature by proposing an OCB model which has transactional leadership, organizational justice, and psychological ownership as independent variables; perceived organizational support, and mentoring as mediating and moderating variables respectively. The model also aimed at contributing a workable process toward effective transformation of Power Holding Company of Nigeria (PHCN). The study is therefore important because it contains some major contributions to organizational behavior literature primarily through employing moderating variable of mentoring, and inclusion of three independent variables as correlates to perceived organizational support. Practically, the model will be relevant to the current effort of the Federal Republic of Nigeria to transform the PHCN. The effective functioning of PHCN is important for developing all sectors of the Nigerian economy.